2023
DOI: 10.3389/fendo.2022.1095211
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related kidney disease: Beyond hypertension and insulin-resistance

Abstract: Chronic kidney disease (CKD) causes considerable morbidity, mortality, and health expenditures worldwide. Obesity is a significant risk factor for CKD development, partially explained by the high prevalence of diabetes mellitus and hypertension in obese patients. However, adipocytes also possess potent endocrine functions, secreting a myriad of cytokines and adipokines that contribute to insulin resistance and induce a chronic low-grade inflammatory state thereby damaging the kidney. CKD development itself is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 245 publications
(287 reference statements)
0
15
0
Order By: Relevance
“…For frail components, there was an interesting discovery that weight loss was associated with a higher risk of CKD. Previous studies have found that obesity was a driver of CKD progression, and the mechanisms included hemodynamic changes, in ammation, oxidative stress, and activation of the renin-angiotensinaldosterone system (RAAS) (19,20). Weight loss and RAAS blockers have a protective effect on obesityrelated CKD (21).…”
Section: Discussionmentioning
confidence: 99%
“…For frail components, there was an interesting discovery that weight loss was associated with a higher risk of CKD. Previous studies have found that obesity was a driver of CKD progression, and the mechanisms included hemodynamic changes, in ammation, oxidative stress, and activation of the renin-angiotensinaldosterone system (RAAS) (19,20). Weight loss and RAAS blockers have a protective effect on obesityrelated CKD (21).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 However, adipocytes also possess potent endocrine functions, secreting a myriad of cytokines and adipokines that contribute to insulin resistance. 48 Dietary pattern should be adapted to appropriate calorie requirements, personal and cultural food preferences, and nutritional therapy for other medical conditions. One way to achieve this is by following plans such as the Dietary Approaches to Stop Hypertension (DASH) diet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, WAT dysfunction due to metabolic disorders has a role in CKD development, progression, and co-morbidities. Specifically, the role of obesity-related adipose tissue dysfunction in the promotion and maintenance of kidney disease has been extensively reviewed and is outside of the scope of this mini-review [131][132][133] . Adipose tissue dysfunction in advanced kidney disease and obesity share similarities as most of the key cytokines, metabolites, and hormones that are dysregulated in uremia have been demonstrated to cause kidney injury in obesity models as well.…”
Section: Adipose Tissue Dysfunction and Ckd Progressionmentioning
confidence: 99%